Blood biomarkers for vascular cognitive impairment based on neuronal function: a systematic review and meta-analysis - Weiquan Huang; Libin Liao; Qian Liu; Rongchao Ma; Xuan He; Xuan He; Xiaoqiong Du; Dujuan Sha; Dujuan Sha; Dujuan Sha; Dujuan Sha (Frontiers in Neurology)
Vascular cognitive impairment (VCI) is increasingly recognized as the second most prevalent cause of dementia, primarily attributed to vascular risk factors and cerebrovascular disease. Numerous studies suggest that blood biomarkers may play a crucial role in the detection and prognosis of VCI. This study conducted a meta-analysis to evaluate the potential of various blood biomarkers associated with neuronal function as indicators of VCI. We searched four major databases—PubMed, Embase, Web of Science, and the Cochrane Library—up to December 31, 2023, for research on blood biomarkers for VCI. Of the 4,043 studies identified, 30 met the inclusion criteria for this review. The nine peripheral biomarkers analyzed for their association with neuronal function include amyloid beta 42 (Aβ42), amyloid beta 40 (Aβ40), Aβ42/Aβ40 ratio, total Tau (t-Tau), phosphorylated tau 181 (p-tau 181), neurofilament light (NfL), brain-derived neurotrophic factor (BDNF), S100B, and soluble receptor for advanced glycation end products (sRAGE). Our findings reveal that peripheral Aβ42, Aβ42/Aβ40 ratio, NfL, and S100B significantly differ between VCI and non-VCI groups, indicating their potential as blood biomarkers for VCI.